A successful pregnancy with severe male and female factor infertility treated with laser-assisted thinning - Subhendu Pandit; Prashant Sharma; Hrishikesh Magdum; Rachna Gulati; Manish Singh Ahuja (Journal of Clinical and Scientific Research)
Lifestyle changes have brought about a surge in the incidence of infertility due to both male and female factors. Although newer treatment modalities continue to boom, maternal age, in vitro culture conditions and cryopreservation affect the elasticity and thinning of the zona, which may affect hatching and subsequent implantation – keeping the rates of success low. Assisted hatching using lasers is said to have provided additional support for hatching and implantation in fresh and frozen in vitro fertilisation and intracytoplasmic sperm injection-embryo transfers cycles. Here, we report one such case where a couple reported with inability to conceive for 8 years after marriage and successfully managed with assisted reproductive techniques (laser thinning) for both male and female factor infertility.